Influence of different aluminum salts on the photocatalytic properties of Al doped TiO2 nanoparticles towards the degradation of AO7 dye - Jin-ling Luo (Nature Portfolio, 2017)
Abstract Three kinds of Al-TiO2 samples and pure TiO2 samples were synthesized via a modified polyacrylamide gel route using different aluminum salts, including Al2(SO4)3∙18H2O, AlCl3, and Al(NO3)3∙9H2O under identical conditions. The influence of different aluminum salts on the phase purity, morphologies, thermal stability of anatase and photocatalytic properties of the as-prepared Al-TiO2 nanoparticles were studied. The energy gap (Eg) of Al-TiO2 nanoparticles decreases due to Al ion doping into TiO2. The photocatalytic activities of the Al-TiO2 samples were investigated by the degradation of acid orange 7 dye in aqueous solution under simulated solar irradiation. The Al-TiO2 nanoparticles prepared from Al(NO3)3∙9H2O exhibit the best photocatalytic activity among the four kinds of samples, followed in turn by the Al-TiO2 nanoparticles prepared with AlCl3, Al2(SO4)3∙18H2O and pure TiO2. The different performances are attributed to complex effects of Eg, particle size, surface morphology, phase purity and the defect sites of the Al-TiO2 nanoparticles.